Artificial Intelligence and Spirituality. - Calderero Hernández, José Fernando (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
Drawing from a conceptual review of the terms ‘mind’, ‘intelligence’, ‘spirit’, ‘spirituality’, ‘spiritual intelligence’ and their possible interrelations, an approach to the concept ‘human nature’ is made in relation to transhumanism and post-humanism. In addition, through a reflection on the nature and meaning of the terms ‘datum’, ‘coding’, ‘language’, ‘energy’, ‘concrete’, and ‘abstract’, some dimensions of ‘artificial intelligence’ (AI) and their analogies and differences with ‘the spiritual’ are shown. After a brief foray into the concept of ‘reality’ and its probable ‘fuzziness’, we discuss their intrinsic and inherent mutability, and the possible existential dependence of some of their parts on the intentional activity of personal beings. We point out the dangers, for intellectual rigor and therefore for life in general, and human life in particular, of reductionist interpretations of reality that, arguing at having been scientifically proven, are intended to provide a closed and indisputable explanation of facts and phenomena of diverse aetiology, ignoring the need for ‘management of the unknown’. Consequently, an open, synergetic, harmonious vision of the role of technology and the humanities, especially those most focused on the study of the intangible, is necessary for the progress of knowledge and, therefore, for the mutually beneficial care of humanity and nature.